A report on the SID/NISER Conference on alternative Development Strategies and lifestyles in the ECOWAS Sub-Region - Central Bank of Nigeria (Lagos : Central Bank of Nigeria, 1979)
This is a report containing the conference papers and the minutes thereon.
Includes bibliographical references
hza 01/02/2019
Loans
Keywords: Conference committees; Legislative bodies